1992
DOI: 10.1113/jphysiol.1992.sp019217
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of cardiac noradrenaline spillover and sympathetic outflow to skeletal muscle in humans.

Abstract: SUMMARY1. Muscle sympathetic nerve activity (MSA) was recorded in the peroneal nerve at the knee by microneurography in ten healthy subjects and determinations were made simultaneously of intra-arterial blood pressure, and whole-body and cardiac noradrenaline spillover to plasma. Measurements were made at rest, during isometric handgrip at 30% of maximum power and during stress induced by forced mental arithmetic.2. At rest there were significant positive correlations between spontaneous MSA (expressed as numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(212 citation statements)
references
References 29 publications
14
193
1
4
Order By: Relevance
“…Support for the concept of a reduction in cardiac sympathetic drive in patients with LQTS emerges: first, from the slower heart rates; second, from the lower LF and LF/HF of RR variability; and third, from evidence that lower levels of MSNA are consistently and strongly associated with low levels of cardiac norepinephrine spillover 13,14 and decreased levels of coronary sinus norepinephrine. 13 Thus, this constellation of findings is very suggestive of a decreased level of cardiac sympathetic drive in patients with untreated LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the concept of a reduction in cardiac sympathetic drive in patients with LQTS emerges: first, from the slower heart rates; second, from the lower LF and LF/HF of RR variability; and third, from evidence that lower levels of MSNA are consistently and strongly associated with low levels of cardiac norepinephrine spillover 13,14 and decreased levels of coronary sinus norepinephrine. 13 Thus, this constellation of findings is very suggestive of a decreased level of cardiac sympathetic drive in patients with untreated LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, in normal subjects a correlation has been reported between MSNA and the sympathetic drive to the heart and the kidney as assessed by norepinephrine spillover rate. 37,38 Also, in EHT patients an increase of MSNA as well as the sympathetic drive to the heart and the kidney have been reported 8 indicating a generalized activation of the sympathetic drive. Indeed, there have been reports using indirect indices of sympathetic nerve activity showing that men have a predominance of sympathetic effects on the heart interval using spectral analysis, 39,40 and higher circulating catecholamine levels than women.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 97%
“…There is a relationship between rising blood pressure and heightened MSNA (27). Wallin et al reported that there were significantly positive correlations between spontaneous MSNA and both spillover of noradrenaline from the heart and concentration of noradrenaline in coronary sinus venous plasma (28). Thus, measurement of MSNA is a useful method for determining the sympathetic nerve activity in human hypertension, whereas it provides no direct information regarding sympathetic nerve activity to other organs such as the kidney and heart.…”
Section: Effects Of Low-dose Atropine On Cardiac Vagal Activitymentioning
confidence: 99%